Effect of Age on the Profile of Psychotropic Users: Results from the 2010 National Ambulatory Medical Care Survey. Issue 2 (13th January 2014) - Maust, Donovan T.; Oslin, David W.; Marcus, Steven C.
<x xml:space="preserve">Abstract</x> Objectives To describe the effect of age on psychotropic coprescribing, psychiatric diagnoses, and other clinical characteristics. Design Analysis of the National Ambulatory Medical Care Survey. Setting A national sample of outpatient visits to physicians (N = 2, 406) in office‐based practice in 2010. Participants Adults prescribed psychotropic medication (N = 31, 229). Measurements Office visits at which antidepressant, anxiolytic, sedative, hypnotic, antipsychotic, or mood stabilizer medications were prescribed were grouped according to participant age (21–64, ≥65) and then compared within each medication class on visit characteristics. and then compared according to variables including provider type, sex, and race; presence of diagnosed mental illness; prescription of other psychotropic agents; total number of chronic conditions; time spent with physician; and total number of medications. Results In 2010, there were 90.3 million antidepressant office visits; 77.7 million anxiolytic/sedative/hypnotic visits; 15.5 million antipsychotic visits; and 9.5 million mood stabilizer visits. Nonpsychiatrists prescribed the majority of psychotropic medications for every class and age group; 17.3% of older adult antipsychotic visits and 44.9% of younger adult antipsychotic visits were to a psychiatrist (chi‐square = 19.58, P = .001). Older adults in every medication class were less likely to have a diagnosed mental disorder. Conclusion Older adults prescribed psychotropic medication were less likely to have a diagnosed mental disorder than their younger counterparts. Efforts to promote quality prescribing should seek to minimize nonspecific use of psychotropic medication.